x(x+3)-6(x+3)=0

Simple and best practice solution for x(x+3)-6(x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+3)-6(x+3)=0 equation:


Simplifying
x(x + 3) + -6(x + 3) = 0

Reorder the terms:
x(3 + x) + -6(x + 3) = 0
(3 * x + x * x) + -6(x + 3) = 0
(3x + x2) + -6(x + 3) = 0

Reorder the terms:
3x + x2 + -6(3 + x) = 0
3x + x2 + (3 * -6 + x * -6) = 0
3x + x2 + (-18 + -6x) = 0

Reorder the terms:
-18 + 3x + -6x + x2 = 0

Combine like terms: 3x + -6x = -3x
-18 + -3x + x2 = 0

Solving
-18 + -3x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-3 + -1x)(6 + -1x) = 0

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6

Solution

x = {-3, 6}

See similar equations:

| (y-x)(y+11x)=a^2-b^2 | | c+8+2c=-10 | | -60=-6+6a | | (y-x)(y+11x)=y^2-x^2 | | -0.151-0.008n=4.1 | | 3y-9+3-4y=y+y-18 | | -0.151=-0.008x+4.15 | | 8.3x-3.1(x-4)=-29.04 | | X=0.75+0.35 | | (x-5)(4x-9)=0 | | 5+1.5(d-1)=0.5 | | n^2+4n-10=0 | | 12m=20m+80 | | 3-4(x-2)=8x(2x-1) | | 4(x-3)+8=4(2x-6) | | (x+2)-(59-x)= | | 5-4a=a-13+-1a | | p=36inches | | (x+2)+(59-x)= | | m/2-3=-18 | | 3(10*2x)=25 | | j+j-12=2(j-12)+(2(j-12))-4 | | xy-5=2y+8 | | y=1.4x+4.4 | | -45=-2x-3+8x | | (2x+8)+(3x-28)= | | 5x-4(x+3)=7x+14 | | j+j-12=2(j-12)+2(j-12)+-4 | | 5v-32=8(v-7) | | X=2.5+2.8 | | ([2/3]*[v])^-3 | | 5x+y=o |

Equations solver categories